(untitled) (Research, Society and Development, 2021)
Plant Physiology is one of the areas of Botany that is concerned with studying how plants grow, develop and function within their habitat. Endowed with many terms and processes, this area is seen by many students as complex and tedious. To circumvent this problem, the present work has as main objective to facilitate and motivate the learning of students in the discipline of Biology, in High School, more precisely within Plant Physiology, with regard to the topic of abiotic stress in maize plants (Zea mays L.) In this way, the proposed practical activity allows the student to work with simple and low-cost materials and to analyze the effects of abiotic stressors such as the salt stress factor, stress by extremely pH, acid pH and water stress in young maize plants. Thus, the practical activity in question allows to promote a greater interest of the students, facilitating the contextualization besides allowing the work of the scientific experimentation.